Emergency Nursing Care for Patients with a Medical Diagnosis of Closed Fracture : Case Study - Rafi Uma Adjiputra Wiryadi; Yeni Kartika Sari; RR Dewi Rahmawaty AP; Erni Setiyorini (Health Gate, 2026)
Background: a fracture is a break in the movable bone network caused by a stronger external force. Several other factors can cause a fracture, including injury, mechanical stress, or bone abnormalities that weaken the bone. Immediate treatment for clients who experience broken bones is one of the problems frequently encountered in the emergency room. Objective: this final report aims to analyze the implementation of emergency care and to provide appropriate emergency care for clients with closed fractures in the Emergency Department of Aminah Blitar Hospital, including assessment, surgical diagnosis, intervention, and postoperative evaluation. Methods: the method used was a case study with a hemorrhage care approach. Data collection was through interviews, observation, physical examination, and documentation review during clinical practice in the Emergency Department of Aminah Blitar Hospital. The assessment results indicated that the patient experienced musculoskeletal system disorders with primary problems of acute pain, impaired physical mobility, and risk of infection. The hemorrhage interventions provided included pain management, physical mobility support, infection prevention, and collaboration with the medical team. Nursing care was implemented in accordance with emergency priorities, resulting in an improvement in the patient's condition. Results: evaluation of nursing outcomes indicated that the treatment objectives were largely achieved. Conclusion: this report concludes that appropriate implementation of emergency nursing care for patients with near-fracture fractures can improve comfort and mobility and prevent further complications.